The Influence of Organizational Citizenship Behavior (OCB) and Quality of Work Life (QWL) on Employee Performance at PT. Milan Ecowood Indonesia in Tangerang - Robby Kharisma; Wahadi Siamto; Kenny Astria (Journal of Research in Business, Economics, and Education, 2022)
The purpose of this study includes to determine the partial effect of Organizational Citizenship Behavior (OCB) on the performance of employees at PT. Milan Ecowood Indonesia in Tangerang, to determine the partial effect of Quality Of Work Life (QWL) on employee performance at PT. Milan Ecowood Indonesia in Tangerang and to determine the simultaneous influence of Organizational Citizenship Behavior (OCB) and Quality Of Work Life (QWL) on employee performance at PT. Milan Ecowood Indonesia in Tangerang. The stages of this research method are gradually adjusted to the level of the author's needs, starting with an introduction in the form of writing a research title proposal, seminar proposal, improving the proposal, making research instruments, collecting primary and secondary data, processing data that has been obtained by the author. and preparation of research reports. The methods used are Validity, Reliability, Classical Assumptions, Hypotheses, Multiple Regression Analysis and Coefficient of Determination. This analysis test uses SPSS version 20. Partial research results OCB has an effect on employee performance and QWL also affects employee performance.